MOTIVASI BELAJAR ONLINE MATEMATIKA MAHASISWA BERDASARKAN GENDER - Fitriani Nur; Rara Aprilyanti (AN-NISA, 2022)
This study aims to describe students' motivation to learn mathematics based on gender during online learning. The type of research used is descriptive quantitative, involving students of mathematics education study program through filling out a questionnaire instrument for learning mathematics. The data obtained were analyzed using descriptive statistics, then the research results obtained include: the mathematics learning motivation of female and male students is in the medium category. However, when viewed from every aspect of motivation to learn mathematics, female students have higher motivation than male students during online learning. So it is recommended that mathematics learning pays attention to collaboration based on gender.Penelitian ini bertujuan untuk mendeskripsikan motivasi belajar matematika mahasiswa berdasarkan gender selama pembelajaran online. Jenis penelitian yang digunakan yaitu kuantitatif deskriptif, dengan melibatkan mahasiswa prodi pendidikan matematika melalui pengisian instrumen angket motivasi belajar matematika. Data yang diperoleh dianalisis menggunakan statistik deskriptif, kemudian diperoleh hasil penelitian antara lain: motivasi belajar matematika mahasiswa perempuan dan laki-laki berada pada kategori sedang. Tetapi, jika ditinjau dari setiap aspek motivasi belajar matematika, mahasiswa perempuan memiliki motivasi yang lebih tinggi dibandingkan dengan mahasiswa laki-laki selama pembelajaran online. Sehingga direkomendasikan pembelajaran matematika yang memperhatikan kolaborasi berdasarkan gender.